DNA Methylation and the Evolution of Developmental Complexity in Plants - Bräutigam, Katharina; Cronk, Quentin (Frontiers in Plant Science, 2018)
All land plants so far examined use DNA methylation to silence transposons (TEs). DNA methylation therefore appears to have been co-opted in evolution from an original function in TE management to a developmental function (gene regulation) in both phenotypic plasticity and in normal development. The significance of DNA methylation to the evolution of developmental complexity in plants lies in its role in the management of developmental pathways. As such it is more important in fine tuning the presence, absence and placement of organs rather than having a central role in the evolution of new organs. Nevertheless, its importance should not be underestimated as it contributes considerably to the range of phenotypic expression and complexity available to plants: the subject of the emerging field of epi-evodevo. Furthermore, changes in DNA methylation can function as a “soft” mutation that may be important in the early stages of major evolutionary novelty.